Thyrotoxic Cardiomyopathy as the Cause of Congestive Heart Failure in a 32-Year-Old Woman: A Case Report - Muhammad Arif Dwitama; Elsa Nabila Yumeza (International Medical Journal Corp. Ltd, 2026)
Introduction : Thyrotoxic cardiomyopathy represents a potentially reversible form of cardiomyopathy precipitated by prolonged or severe excess of thyroid hormones, leading to high-output cardiac failure, arrhythmias, and ultimately myocardial dysfunction. Its occurrence in young women without prior cardiovascular comorbidities remains a clinically underrecognized emergency. This case report aims to highlight the pathophysiological interplay between thyroid hormone excess and acute congestive heart failure (CHF) in a young female patient presenting to a secondary-level hospital in Indonesia. Case Illustration : A 32-year-old female with no prior medical history presented with a three-week history of progressive dyspnea on exertion, orthopnea, epigastric discomfort, and fatigue. On admission, she was found to have a ventricular rate of 240 beats per minute, oxygen saturation of 95% on room air, diffuse pulmonary crackles, and a palpable thyroid enlargement. The Wayne Index was 19. Thyroid function tests revealed a markedly elevated free thyroxine (FT4) of 61 pmol/L and suppressed thyroid-stimulating hormone (TSH) of 0.10 mIU/L. Electrocardiography demonstrated ventricular rate of 210 bpm with subsequent confirmation of atrial fibrillation with rapid ventricular response (AF RVR). Chest radiography demonstrated cardiomegaly with pulmonary edema and bilateral pleural effusion. She was managed in the Intensive Care Unit with antithyroid therapy (thiamazole 2×20 mg), intravenous amiodarone infusion per protocol, furosemide, propranolol, and supportive care. Following 10 days of comprehensive management, she achieved clinical remission with normalized heart rate, resolution of dyspnea, and hemodynamic stability, and was successfully discharged. Discussion : Thyroid hormone excess exerts direct chronotropic, inotropic, and lusitropic effects on the myocardium via genomic and non-genomic mechanisms, including upregulation of alpha-myosin heavy chain, sarcoplasmic reticulum Ca²⁺-ATPase (SERCA2a), and downregulation of phospholamban. These effects, coupled with peripheral vasodilation and neurohormonal activation, establish the substrate for high-output heart failure, atrial fibrillation, and eventually systolic dysfunction — the hallmarks of thyrotoxic cardiomyopathy. Early diagnosis using validated scoring tools (Burch-Wartofsky Point Scale, Wayne Index) and prompt multimodal therapy are critical to prevent multiorgan failure. Conclusion : This case underscores the importance of thyroid function evaluation in young patients presenting with new-onset atrial fibrillation and heart failure, particularly in the absence of conventional cardiovascular risk factors. Thyrotoxic cardiomyopathy is a reversible condition when diagnosed promptly and treated with antithyroid agents, appropriate rate control, and diuresis.